1935
DOI: 10.3181/00379727-32-7795c
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Determination of Gum Acacia in Blood. Rate of Disappearance in Normal Dogs

Abstract: From the Pharmaco1o;gical La'boratorg, University of CaZif0mk.z Medical School, Salt Fran&co, Odif o m b .In the use of gum acacia in the treatment of nephrosis it is important to maintain a definite minimum concentration in the blood stream in order to derive satisfactory results. There is, therefore, need of a method for an accurate quantitative estimation of acacia on a sufficiently small sample of Wood so that the test may be frequently repeated, especially when small children are involved. Acacia is a pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1937
1937
1973
1973

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The results show that a considerable amount of acacia has remained in the blood of dogs for as long as 144 days. Other workers (7,12,13) have indicated that gum acacia in appreciable quantities disappears from the blood of various animals in relatively short periods of time up to 5 to 7 days. All of such observations, the present included, obviously are dependent upon the quantity of the gum injected, the number of injections, and the elapsed time from the first to the last injection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results show that a considerable amount of acacia has remained in the blood of dogs for as long as 144 days. Other workers (7,12,13) have indicated that gum acacia in appreciable quantities disappears from the blood of various animals in relatively short periods of time up to 5 to 7 days. All of such observations, the present included, obviously are dependent upon the quantity of the gum injected, the number of injections, and the elapsed time from the first to the last injection.…”
Section: Discussionmentioning
confidence: 96%
“…Concentration of gum acacia solution in whole blood and plasma was determined spectrophotometrically following the principles of the method described by Peoples and Phatak (13).…”
Section: Methodsmentioning
confidence: 99%
“…Gum acacia was diluted in Locke's solution (minus calcinm chloride) to a concentration of 12 per cent and injected by vein. Concentration of gum acacia solution in whole blood was determined spectrophotometrically following the principles of the method described by Peoples and Phatak (6). Vi~min E is a mixture of distilled natural tocopherols.…”
Section: Methodsmentioning
confidence: 99%
“…Concentration of gum acacia solution in whole blood was determined spectrophotometrically following the principles of the method described by Peoples and Phatak (6). Vi~min E is a mixture of distilled natural tocopherols.…”
Section: Idver Extract With Iron Is Designated "Lextron" (Liver-stomamentioning
confidence: 99%